Neutrophil-Lymphocyte Ratio (NLR) as an output-outcome predictor in moderate-severe head injury at Sanglah General Hospital, Denpasar, Indonesia - Melissa Krisanty; Tjokorda Gde Bagus Mahadewa; I Wayan Niryana; I Nyoman Semadi; I Gede Suwedagatha; I Gusti Agung Bagus Krisna Wibawa (DiscoverSys Inc., 2021)
Background: This prospective cohort study aims to determine the best cut point value and the ability to predict Neutrophil Lymphocyte Ratio (NLR), analyze the most dominant factors, and the direct influence of the NLR to output and outcome in moderate and severe trauma to the head injury at Sanglah General Hospital, Denpasar, Indonesia.Methods: This study was an observational analytic with a prospective cohort design. The subjects of this study were head injury patients over 16 years old with Glasgow Coma Scale (GCS) ? 12 who visited and were treated at Sanglah General Hospital, Denpasar, Indonesia. Patients less than 16 years old, history of alcohol intoxication, stroke, metabolic disease, and multiple traumas were not included as research subjects. Data were analyzed using SPSS version 20 for Windows.Results: The research conducted on 49 respondents found that the best cut-off point of NLR was 6.05 has the most significant predictor (OR=7.6; p=0.001) and dominant (OR=64.97; p=0.002) factors to the output-outcome predictor in moderate-severe head injury. In addition, this cut-off value (6.05) also has a direct influence (x-value=0.523) in the occurrence of output and outcome unfavorable in moderate-severe head injury.Conclusion: the cut-off NLR values of 6.05 became the dominant predictor that directly affected the output and outcome unfavorable in moderate-severe head injury.